Pelatihan Internalisasi Penguatan Peran Perempuan (Istri Pejabat) dalam Pembangunan Budaya Integritas - Grashinta, Aully; Aini, Farida; Kistyanti, Ni Made Rai; P.H., Fasya Azzahra (Fakultas Psikologi Universitas Pancasila, 2023)
Corruption is a phenomenon that still occurs in Indonesia. This condition encourages concrete steps to be taken so that acts of corruption can be prevented, one of which is by involving the role of officials' wives in the government environment. It is considered important for wives to be involved in preventing and eradicating corruption because basically, wives have a big influence on the decisions taken by their husbands, who in this case are in office. Therefore it was held